Feasibility of hyperthermic intraperitoneal chemotherapy (HIPEC) in ovarian cancer during COVID‐19 pandemic. Issue 6 (June 2021) - Ayhan, Ali; Baran, Safak Yilmaz; Vatansever, Dogan; Durdag, Gulsen Dogan; Akilli, Huseyin; Celik, Husnu; Taskiran, Cagatay
ABSTRACT : Objective : This study aims to evaluate the effect of the COVID‐19 pandemic and related restrictions on patients who underwent cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (HIPEC) for ovarian cancer. Methods : We retrospectively evaluated ovarian cancer patients who underwent HIPEC following complete cytoreductive surgery performed during the outbreak of the COVID‐19 pandemic in three different centers specializing in gynecological oncology. All patients who underwent cytoreduction plus HIPEC for a primary, interval, and recurrent surgery were evaluated. Primary outcomes was postoperative 30‐day morbidity and mortality. The secondary outcome was infection of patient and/or related staff with COVID‐19 during the perioperative or early postoperative period. Results : We performed a total of 35 HIPEC procedures during the pandemic: 15 (42.9%) patients underwent primary/interval surgery, while 20 (57.1%) patients had recurrent disease. Grade 3‐4 complications occurred in one patient (2.9%) (chronic renal failure), while mortality did not occur in any patient. Neither the patients nor related staff were infected with the coronavirus during the perioperative or early postoperative period. One patient, who was diagnosed with COVID‐19 pneumonia on postoperative day 80 died from the infection. Another patient died on postoperative day 85 due to progressive ovarian cancer, a disorder in vital functions, and organ failure. Conclusion : HIPEC during the COVID‐19 pandemic seems a safe and feasible procedure, with acceptable morbidity and mortality rates. Careful selection of patients is important and precautions should be taken before the procedure.